Vibrant Energy Aware Spray and Wait Routing in Delay Tolerant Network - Viren G. Patel; Tushar K. Oza; Dhavalsinh M. Gohil (Journal of Telematics and Informatics, 2013)
Delay tolerant networks (DTN) are wireless networks where disconnections arise often due to the mobility of nodes, failures of energy, the low density of nodes, or when the network extends over long distances. In these situations, traditional routing protocols that have been developed for mobile ad hoc networks prove to be unsuccessful to the scope of transmitting messages between nodes. The Spray and Wait routing may achieve low routing and energy efficiency due to the blindness in the spray phase. To deal with this situation, we propose an opportunistic routing with enclosed message copies, called the Vibrant Energy aware Spray and Wait (VESW), which utilizes the information about vibrancy of node and remaining energy to allocate the number of copies between the corresponding pair nodes in the spray phase.